2004
DOI: 10.1016/j.annemergmed.2004.09.003
|View full text |Cite
|
Sign up to set email alerts
|

ABSCESS: Applied bedside sonography for convenient evaluation of superficial soft tissue infections

Abstract: of the use of ultrasonography to evaluate lateral malleolar injuries performed the studies. The physicians were asked after performing the ultrasonography whether they believed there was a fracture. Their responses were then compared with the radiologist's interpretation of the radiograph.Results: There were 12 ultrasonographic examinations performed by emergency attending physicians; 8 were interpreted as negative, and none of these had fractures identified on radiograph. Four were interpreted as positive, 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 29 publications
0
40
0
1
Order By: Relevance
“…Three Delphi rounds were conducted to reach a consensus. These 16 topics included measurement of the height of the internal jugular vein, 29,30 inferior vena cava measurement, 31,32 pleural effusion and thoracentesis, 8,33,34 central line insertion and pneumothorax, 3,6,7,35,36 liver and spleen examination, 2,37 ascites and paracentesis, 9,38 the bladder, 14,39,40 cellulitis/abscess/aspirates, 41,42 arterial line insertion, 43 peripheral intravenous access, 44,45 and joint aspiration. 10 Although the evidence for the role of ultrasound in establishing peripheral intravenous access in adults is not as consistent as that in pediatric patients, 46 the group felt that learning this skill is unlikely to be harmful and may improve the care of patients.…”
Section: Resultsmentioning
confidence: 99%
“…Three Delphi rounds were conducted to reach a consensus. These 16 topics included measurement of the height of the internal jugular vein, 29,30 inferior vena cava measurement, 31,32 pleural effusion and thoracentesis, 8,33,34 central line insertion and pneumothorax, 3,6,7,35,36 liver and spleen examination, 2,37 ascites and paracentesis, 9,38 the bladder, 14,39,40 cellulitis/abscess/aspirates, 41,42 arterial line insertion, 43 peripheral intravenous access, 44,45 and joint aspiration. 10 Although the evidence for the role of ultrasound in establishing peripheral intravenous access in adults is not as consistent as that in pediatric patients, 46 the group felt that learning this skill is unlikely to be harmful and may improve the care of patients.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, US can distinguish solid lesions from cystic ones, and among these, it contributes to differentiating abscesses from other conditions such as cellulitis, foreign bodies, or fasciitis, leading to proper treatment [76][77][78].…”
Section: Soft-tissue Abscessesmentioning
confidence: 99%
“…Owing to its high sensitivity, even in comparison with CT scans, US is considered the imaging of choice for diagnosis and treatment of soft tissue conditions, as assessed in the ABSCESS (applied bedside sonography for convenient evaluation of superficial soft tissue infections) prospective clinical trial [76]. In fact, US can distinguish solid lesions from cystic ones, and among these, it contributes to differentiating abscesses from other conditions such as cellulitis, foreign bodies, or fasciitis, leading to proper treatment [76][77][78].…”
Section: Soft-tissue Abscessesmentioning
confidence: 99%
“…The sonographic features of abscesses have been described previously, 7,[9][10][11][12] and they include findings such as the presence of interstitial fluid, characteristics of abscess debris, and depth of abscess cavity. These sonographic findings represent visualization of physiologic changes such as increased subcutaneous edema, changes in viscosity of the abscess purulence, or extent of surrounding induration.…”
mentioning
confidence: 99%
“…3 There are a few previously published prediction rules for the presence of CA-MRSA or MRSA in patients with skin infections using clinical predictors, but these studies have been limited to inpatients 4 or include surveillance nasal cultures, 5 the results of which are not available immediately. Recently, a few studies have demonstrated the utility of bedside soft tissue ultrasound (US), [6][7][8] and it is possible that there are some features of soft tissue US that could be used to predict the presence of CA-MRSA. The benefit of using bedside US is that the findings are available immediately and can be used to direct initial patient care decisions.…”
mentioning
confidence: 99%